‘We had a good laugh together’: using Teams for collaborative learning - Katy Jones (Association for Learning Development in Higher Education (ALDinHE), 2021)
This case study describes the journey of an undergraduate module in its transition from an in-person lectures-plus-seminar configuration to an interactive, online format using Teams. I show how I created a sense of community and the opportunity for online group interaction by establishing small study groups that carried out weekly online group tasks in their own Team ‘channel’. Weekly roles were assigned to group members to spread the workload and ensure equal participation. Student feedback was overwhelmingly positive, and students particularly appreciated the opportunity to interact with their peers, during a potentially lonely time, for summative marks. Limitations to the model are discussed and potential solutions are offered.